Electoral college reform : challenges and possibilities - Bugh, Gary.; Bugh, Gary. (Farnham, Surrey, England ; Burlington, VT. : Ashgate Pub., 2010)
Why hasn't the United States reformed the Electoral College system, and how can it best do so? To address these questions, Electoral College Reform: Challenges and Possibilities brings together new essays by law professors and political scientists examining the reasons for reform, the issues surrounding a Constitutional amendment, the effect of the Electoral College on political campaigns and government policymaking, and the possibilities for extra-Constitutional avenues to change, including the courts and the state legislatures.
Introduction: Approaching electoral college reform / Gary E. Bugh -- Representation in congressional efforts to amend the presidential election system / Gary E. Bugh -- "Mere deception, a mere ignus fatus on the people of America" : lifting the veil on the electoral college / Michael T. Rogers -- "If the manner of it be not perfect" : thinking through electoral college reform / Michael J. Korzi -- Electoral college and democratic responsiveness / Jeffrey M. Stonecash -- Challenge of contemporary electoral college reform / Gary E. Bugh -- Systemic biases affecting congressional voting on electoral college reform / Mark J. McKenzie -- Compact risk : some downsides to establishing national plurality presidential elections by contingent legislation / Brian J. Gaines -- Exploring the difficulties of electoral college reform at the state level : Maine and Nebraska lead the way / James P. Melcher -- Comparative presidential selection : a cautionary tale / Jody C. Baumgartner and Rhonda Evans Case -- Lobbying the electoral college : the potential for chaos / Robert M. Alexander -- Electoral college incentives and presidential actions : a case for reform? / Brenden J. Doherty -- Current electoral college reform efforts among the states / Robert W. Bennett -- Good, the better, the best : improving on the "acceptable" electoral college / Paul D. Schumaker -- Pipe dream or possibility? : amending the U.S. constitution to achieve electoral reform / Burdett A. Loomis -- Conclusion: Understanding electoral college reform / Gary E. Bugh.
Errata slip inserted.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Representative government and representation -- United States; Election law -- United States; Electoral college -- United States; Electronic books